EKOWISATA BERBASIS KONSERVASI DAN PEMBERDAYAAN LOKAL DI TAMAN WISATA PANBIL NATURE RESERVE - Chelsea Yuni Luis; Oda I.B. Hariyanto; Dr. Ratih Anggraini (Universitas Multi Data Palembang, 2026)
Batam relies on the Panbil Nature Reserve to balance its industrial environment. This study uses a qualitative approach to evaluate the reserve's ecotourism strategies and community impact based on visitor feedback. The results reveal a sharp contrast: visitors praised the infrastructure and educational paths for preserving the forest’s beauty, aligning perfectly with conservation goals. However, the economic side fell short. Visitors noted a distinct lack of local products and small businesses on-site, suggesting that while locals are hired as staff, they aren't yet empowered as independent entrepreneurs. The study concludes that to create a truly sustainable model, Panbil must bridge this gap. Future success depends on better integrating the community into the creative economy, ensuring locals are not just employees, but active beneficiaries of the tourism ecosystem.